2020
DOI: 10.1021/acsmedchemlett.0c00353
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Ginkgolic Acid Derivatives as SUMOylation Inhibitors

Abstract: SUMOylation has emerged as an important posttranslational modification that has been shown to modulate protein activity associated with various signaling pathways, and consequently, it has emerged as an important therapeutic target. While several natural products have been shown to inhibit enzymes involved in the SUMOylation process, there has been little progress toward the development of more selective and potent SUMOylation inhibitors. Ginkgolic acid was one of the first natural products discovered to inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Recent advances in the development of synthetic inhibitors have enabled more specific and efficient targeting of the SUMO pathway. Synthetic inhibitors of SAE include compound 9, compound 21, various pyrazole and thiazole urea-containing compounds, ML-792, COH000, ML-93, several ginkgolic acid derivatives, and most recently, TAK-981 [267][268][269][270][271][272][273][274][275]. For example, compound 21 and COH000 act in a similar way as the natural SAE inhibitors.…”
Section: Sumo E1 Inhibitorsmentioning
confidence: 99%
“…Recent advances in the development of synthetic inhibitors have enabled more specific and efficient targeting of the SUMO pathway. Synthetic inhibitors of SAE include compound 9, compound 21, various pyrazole and thiazole urea-containing compounds, ML-792, COH000, ML-93, several ginkgolic acid derivatives, and most recently, TAK-981 [267][268][269][270][271][272][273][274][275]. For example, compound 21 and COH000 act in a similar way as the natural SAE inhibitors.…”
Section: Sumo E1 Inhibitorsmentioning
confidence: 99%
“…Brackett et al synthesized ginkgolic acid derivatives with 6–17 carbon chains to reveal the SAR for SUMO E1. 357 The results showed that any alteration of the substitution pattern about the central aromatic ring completely ablated SUMOylation inhibition. All 2,6-disubstituted analogs could inhibit RanGAP1 SUMOylation at the 50 μM concentration, suggesting that unsaturation did not exert a negative effect on SUMOylation inhibition.…”
Section: Bioactivitymentioning
confidence: 96%
“…In addition, a long alkyl chain is required for ginkgolic acid derivatives to inhibit SUMO E1 and an optimal alkyl tail length is 11–13 (6- and 8-carbon analogs were inactive). 357 Ginkgo polysaccharides displayed antitumor activity against SMMC-7721 hepatoma cells, 358 human SGC-7901 gastric cancer cells, 359 and human bladder T24 cancer cells. In addition, a selenium (Se)-containing polysaccharide was isolated and found to induce bladder cancer apoptosis, likely through a mitochondria-dependent pathway.…”
Section: Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…To determine this, we investigated the effect of ginkgolic acid (GA). GA, an extract from Ginkgo biloba leaves, is a type of alkyl phenol that can directly bind SUMO-activating enzyme, E1, and inhibit the formation of the E1-SUMO intermediate, thereby diminishing SUMOylation [136][137][138][139][140]. Because SUMO1 depletion enhanced autophagic activities in HD, we hypothesized that GA might enhance the autophagy activities and alter HTT levels in HD cells.…”
Section: The Sumoylation Inhibitor Ginkgolic Acid (Ga) Enhances Autopmentioning
confidence: 99%